Differences of the Insulin and Brain Derived Neurotrophic Factor Between Normal Born Weight Baby and Baby With Intrauterine Growth Restriction - Tiyan febriyani lestari; Yusrawati Yusrawati; Arni Amir (Universitas Andalas, 2018)
Background: Intrauterine Growth Restriction (IUGR), is a condition in which the fetal growth rate is less than 10 percentiles. Fetal growth is affected by maternal health and nutrition, the hormone insulin and placenta. Placental development is influenced by the Brain Derived Neurotropic Factor (BDNF). Insulin deficiency and BDNF can interfere with fetal development.Method: This study used an observational research method, with a comparative cross sectional design. The place of research was conducted at Bayangkara Hospital, Dr. Rasidin, TK.III Reksodiwiryo Hospital, and Biomedical Laboratory, Faculty of Medicine, Andalas University. Research time starts from October 2017 to January 2018. The sample of this study was 25 normal babies and 25 babies with IUGR. Insulin levels and BDNF were examined by enzyme-linked immunosorbent assay (ELISA). Test the normality of the data using the Kolmogorov-Smirnov test. Statistical analysis using independent t test.Results: Insulin levels of 13.2 ± 1.7 mIU / L in infants with normal birth weight and 8.5 ± 1.7 mIU / L in infants born with IUGR (p = 0.000) and BDNF levels 1.5 ± 0.2 ng / ml for infants with normal birth weight and 1.4 ± 0.3 ng / ml in infants born with IUGR (p = 0.008).Conclusion Insulin levels and BDNF levels of normal birth weight babies are higher than babies born with IUGR.